Pathogenicity of Beauveria bassiana to soybean pest insects - Tonet, Gabriela Lesche; Reis, Erlei Melo (Pesquisa Agropecuaria Brasileira, 2014)
The pathogenicity of Beauveria bassiana (Balsamo) Vuillemim on the soybean Glycine max, L. (Merrill) pest species Nezara viridula (L., 1758) and Diabrotica speciosa (Germar 1824) has been demonstrated in trials conducted in 1976 at Passo Fundo, Rio Grande do Sul State, Brazil under laboratory conditions. Aiming at to obtain the inoculum for field work, the factors influencing fungus esporulation have been studied. It has been demonstrated that culture medium of "Semolina-Ágar", with pH 6.0 and exposed to a photo-period of twelve hours under light and twelve hours in dark, gives the maximum production of inoculum.